2009
DOI: 10.1088/1478-3975/6/3/036010
|View full text |Cite
|
Sign up to set email alerts
|

Palytoxin and the sodium/potassium pump—phosphorylation and potassium interaction

Abstract: We proposed a reaction model for investigating interactions between K+ and the palytoxin-sodium-potassium (PTX-Na+/K+) pump complex under conditions where enzyme phosphorylation may occur. The model is composed of (i) the Albers-Post model for Na+/K+-ATPase, describing Na+ and K+ pumping; (ii) the reaction model proposed for Na+/K+-ATPase interactions with its ligands (Na+, K+, ATP, ADP and P) and with PTX. A mathematical model derived for representing the reactions was used to simulate experimental studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The binding of two PTX molecules may occur only if the pump is a diprotomeric complex [14]. Evidence of the pump functioning as a diprotomer has been reported [15] and, furthermore, the experiments described above [5,6] were carried out in conditions where it is possible to consider the existence of pumps functioning as diprotomeric complexes [15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The binding of two PTX molecules may occur only if the pump is a diprotomeric complex [14]. Evidence of the pump functioning as a diprotomer has been reported [15] and, furthermore, the experiments described above [5,6] were carried out in conditions where it is possible to consider the existence of pumps functioning as diprotomeric complexes [15].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the Na + occlusion/deocclusion in the channel not bound by PTX, reaction p7 is responsible for the transitions between high-and low-level activities in the PTX-induced channels. The effect of the Na + binding to an α chain of the diprotomer was also reported [14]. The author observed that the presence of three Na + in one α chain of the pump, forming the substate (K + ) 2 E2:Na + 3 E1, reduces the transition rate of the second protomer to state E1.…”
Section: Namentioning
confidence: 86%
See 2 more Smart Citations
“…The inward movement of two potassium ions and the extrusion of three sodium ions by the Na/K pump, which is the source of its electrogenic effect, was represented by a fictitious ion A + flowing according to the electrochemical gradient. The intra and extracellular ionic concentrations of this ion were determined by equations representing the Albers-Post model (Rodrigues et al 2008(Rodrigues et al , 2009.…”
Section: The Nonsynaptic Epileptiform Activity Modelmentioning
confidence: 99%